Awareness of Diabetic Retinopathy among Adult Population Attending Rural Health Care Center, Uttar Pardesh - Pragati GARG; Mahrukh KHAN (Modern Medicine)
Purpose: To study the awareness of diabetes and its multisystem involvement like diabetic retinopathy among population attending the rural health care center of a tertiary care hospital. Methods: A cross sectional study over a period of 2 years was conducted amongst 6000 general adult population attending rural health care center of a tertiary care hospital in Uttar Pradesh. All the patients were subjected to random blood sugar testing and a self-made questionnaire. Data obtained was statistically analyzed using SPSS software version 15.0. (P<0.05) was taken as significant value. Results: In our study, we enrolled 6000 participants of mean age 56.4 years +/- 10years with male: female ratio of 3:5. Based on the questionnaire, we observed that 71.05% of the enrolled participants were unaware about the complications of diabetes. 85.03% did not know that diabetes could affect the eyes per say. While more than 92.18% were particularly unaware about diabetic retinopathy or its treatment modalities. 93.3% of the general adult population said that they would get an eye checkup when their vision is significantly reduced. The awareness about diabetic eye disease was significantly less in females. (p<0.05) Conclusions: As per our study, more than half of the individuals lacked any knowledge about multi system involvement in diabetes. They were particularly unaware about the importance of eye screening in diabetes.